Personality and Its Knowledge - Lazauskas, Justinas (Problemos, 1972)
This essential characteristic is largely determined by biological and psychological peculiarities of personality. However, all-round development and conscious activity play a decisive role in its formation. Personality presents a peculiar totality of qualities and experience of an individual and reflects the degree of its conscious development. Upon the critical review of the modem bourgeois cognizance theories of personality the author concludes that possibilities of its cognizance lie in the dialectical unity of the general peculiar and individual and therefore personality should be studied not only in terms of the respective type but in terms of individuality as well.